Comparison of the accuracy of two wound classification systems for diabetic foot ulcer healing - Kharisma Pratama; Suyanto Suyanto; Wida Kuswida Bhakti; Suriadi Jais (Jurnal Keperawatan Padjadjaran, 2025)
Background: Diabetic foot ulcers (DFUs) remain a significant clinical challenge, requiring precise classification systems to aid prognosis and treatment planning. The Wagner classification is widely used but offers limited detail on specific wound characteristics, while the SHID (Suriadi, Haryanto, Imran, Defa) system provides a more comprehensive evaluation but lacks validation. Purpose: This study was designed to evaluate and compare the predictive validity of the Wagner and SHID classification systems in forecasting DFU healing outcomes. Methods: A prospective cohort study was conducted at Kitamura Clinic and Doctor Soedarso Pontianak Hospital between August 2021 and July 2022, involving 89 DFU patients. Both systems were evaluated based on sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and likelihood ratios. Predictive validity was determined using receiver operating characteristic (ROC) curve analysis and the Youden index. Results: A cut-off grade of >2 provided optimal predictive value for both systems. The SHID classification demonstrated a sensitivity of 92%, specificity of 62%, PPV of 27.5%, and NPV of 98%, while the Wagner classification showed a sensitivity of 58%, specificity of 77%, PPV of 28%, and NPV of 92.2%. Positive likelihood ratios were 2.4 for SHID and 2.5 for Wagner. ROC analysis yielded an area under the curve (AUC) of 0.786 (95% CI: 0.69–0.87) for SHID and 0.703 (95% CI: 0.60–0.80) for Wagner. The Youden index was higher for SHID (0.540) compared to Wagner (0.349). Conclusion: Although both systems are effective for predicting DFU healing within 12 weeks, SHID's superior AUC and Youden index suggest greater clinical utility in screening and managing DFUs.